Sleep Disorders Following Mild and Moderate Traumatic Brain Injury - Al-Ameri, Laith Thamer (Brain Sci, 2019)
(1) Background: Sleeping disorders are frequently reported following traumatic brain injury (TBI). Different forms of sleeping disorders have been reported, such as sleepiness, insomnia, changes in sleeping latency, and others. (2) Methods: A case-control study with 62 patients who were victims of mild or moderate TBI with previous admissions to Iraqi tertiary neurosurgical centers were enrolled as the first group, and 158 patients with no history of trauma were considered as the control. All were 18 years of age or older, and the severity of the trauma and sleep disorders was assessed. The Pittsburgh sleep quality index was used to assess sleep disorders with average need for sleep per day and average sleep latency were assessed in both groups. Chi-square and t-test calculations were used to compare different variables. (3) Results: 39 patients (24.7%) of the controlled group experienced sleeping disorders compared to TBI group with 45 patients (72.6%), P-value < 0.00001. A total of 42 patients were diagnosed on admission as having a mild degree of TBI (mean GCS 13.22 ± 1.76) and 20 patients were diagnosed with moderate TBI (mean GCS11.05 ± 1.14. 27). A total of 27 (46.28%) patients with mild severity TBI and 18 patients (90%) of moderate severity were considered to experience sleeping disorders, P-value 0.0339. Each of the mild and moderate TBI subgroups show a P-value < 0.00001 compared to the control group. Average sleep hours needed per day for TBI and the control were 8.02 ± 1.04 h and 7.26 ± 0.58 h, respectively, P-value < 0.00001. Average sleep latency for the TBI and the control groups were 13.32 ± 3.16 min and 13.93 ± 3.07 min respectively, P-value 0.065. (4) Conclusion: Sleep disturbances are more common following mild and moderate TBI three months after the injury with more hours needed for sleep per day and no significant difference in sleep latency. Sleep disturbances increase in frequency with the increase in the severity of TBI.